KESULITAN GURU DALAM PROSES PEMBELAJARAN PADA MATA PELAJARAN SOSIOLOGI DI MADRASAH ALIYAH MUHAMMADIYAH (MAM) PULAU PUNJUNG - Mairani, Lili - (Pendidikan Sosiologi, 2014)
teachers in the learning process must understand the concept of the subjects but the problem happens is teachers do not understand the concept of learning material that will be taught to student. Research aims to describe the causes of the difficulties of teachers in the learning process and the sociology subjects to describe the efforts made teachers in overcoming difficulties in the learning process. Theory used in this study was largely constructivist theory which is strongly associated with the research pertained ini. jenis research on qualitative descriptive study in which location in .informan in this study is a teacher who teaches sociology, students MAM and MGMP chairman, vice-curriculum, by purposive sampling technique then the data collection methods of observation, interviews and dokumentasi. Activity interviews were conducted with the help of an interview guide, the study analyzed the data through three stages: data reduction, data display and drawing conclusions according to the indrus Miles and Huberman (2009: 148 ). Results of the study are: (1) lack of learning resources (2) MGMP sociology less goes well (3) teachers rarely attend training (4) home study limited time.four factors obtained from the results of this study make it difficult for the teacher in the learning process so that teachers seek for overcome. effort that teachers are (1) to form a study group of fellow teachers (2) to establish communication with the district and the level MGMP western Sumatra (3) controls the use of IPTEK ( Ilmu Teknologi dan Komunikasi )